2012
DOI: 10.4103/0970-9290.107382
|View full text |Cite
|
Sign up to set email alerts
|

Autoclaving and clinical recycling: Effects on mechanical properties of orthodontic wires

Abstract: Although recycle wires were softer than those of control group, relatively small differences and also various properties of available wires have obscured the clinical predictability of their application. There is seemingly no problem in terms of mechanical properties to recycle orthodontic wires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Furthermore, several studies reported asymptomatic carriers, including children, who comprise a high percentage of orthodontic patients, which elevates the risk on the orthodontic team even higher. 5,14,19 Although cross-transmission of COVID-19 within a dental facility has not been reported so far, considering the recent onset of the disease and deficiency in data, the risk is still elevated. Previous studies have reported crosstransmission of infection within the dental facilities including Hepatitis B and Hepatitis C. [20][21][22][23] In the United States, orthodontists are ranked the secondhighest incidence of acquiring Hepatitis B.…”
Section: Risk Of Disease Transmission Within the Orthodontic Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several studies reported asymptomatic carriers, including children, who comprise a high percentage of orthodontic patients, which elevates the risk on the orthodontic team even higher. 5,14,19 Although cross-transmission of COVID-19 within a dental facility has not been reported so far, considering the recent onset of the disease and deficiency in data, the risk is still elevated. Previous studies have reported crosstransmission of infection within the dental facilities including Hepatitis B and Hepatitis C. [20][21][22][23] In the United States, orthodontists are ranked the secondhighest incidence of acquiring Hepatitis B.…”
Section: Risk Of Disease Transmission Within the Orthodontic Practicementioning
confidence: 99%
“…Orthodontic supplies and instruments: Although most archwires are packaged and sealed individually, some orthodontists have recycled and reused wires. 19,39,40 This is a huge risk of crosscontamination if wires are not thoroughly sterilized.…”
Section: Risk Of Disease Transmission Within the Orthodontic Practicementioning
confidence: 99%
“…The rate of using recycled brackets/orthodontic materials was found to be 19.2% (Table 2). In a study published by Oshagh et al (40) in 2012, softening of archwires was reported after sterilization in the autoclave; however, this change was reported to be at low levels and does not pose a problem in clinical practice (40).…”
Section: Discussionmentioning
confidence: 99%
“…Ti and β titanium arch wires following dry heat or cold sterilization method [31][32][33][34][35][36][37][38][39]. Also no significance difference was observed in release of the nickel ion concentration into saliva from recycled Ni TI wires after sterilization with dry heat or steam sterilization [40].…”
Section: Sterilization Of Orthodontic Archwiresmentioning
confidence: 99%